Self-Efficacy Guru Sekolah Dasar dalam Pencegahan dan Intervensi Bullying: Tinjauan Tematik dari Perspektif Perkembangan Anak - Anastasia Arta Uli; Feri Dwi Jayanti; Prince Clinton Immanuel Christian Damanik; Rizki Achmad Husaeni; Mohammad Idham Chaled (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
School bullying affects students' social-emotional development, and the effectiveness of teachers' role in preventing and handling it depends heavily on self-efficacy, teachers' belief in their own capability to manage bullying in the classroom. This article presents a thematic review synthesizing two international systematic reviews (Fischer et al., 2021; van Aalst et al., 2022) together with empirical studies published between 2016 and 2026, extended through the lens of children's cognitive and psychosocial development (Olson et al., 2025; Issawi & Dauphin, 2017). The synthesis shows that teacher self-efficacy is shaped by Bandura's four sources (Pfitzner-Eden, 2016): mastery experience, vicarious experience, social persuasion, and affective states, realized through teaching experience, anti-bullying training, structural school support, and teachers' socio-emotional competence. Teachers with higher self-efficacy are more proactive in addressing physical bullying, though this confidence declines for relational bullying and cyberbullying. Given that primary school children are in Piaget's concrete operational stage and Erikson's industry-versus-inferiority stage, teacher self-efficacy becomes a critical protective factor for students' social-emotional development. The article recommends strengthening simulation-based training, clearer school policies, and further research on self-efficacy instruments sensitive to modern forms of bullying.